The Effect of D/H Aspect Ratio Change on Energy Characteristics of H-type Darrieus Turbine - Nguyen, Quoc Tuan; Nguyen, The Mich; Do, Huy Cuong (Old Journal, 2017)
For the H-type Darrieus turbine runner, the geometry parameters such as runner diameter, blade height, number of blades, D/H ratio, blade profiles... have certain effects on working capacity and the efficiency of the turbine. Therefore in order to provide runner samples with high efficiency and working capability, it is needed to design, simulate and test many runner samples, and then select the most suitable one with real water flow condition. This paper simulates the circumstances on changing D/H aspect ratio of the runner samples, specifically in 03 cases including D/H=0.9, D/H=1 and D/H=1.1 to evaluate the working capacity and efficiency of the turbine, and then to establish the curves on power characteristics of H-type Darrieus turbine. Based on that, we can select the runner sample working better than the remaining samples.